Peningset Making Training in an Effort to Increase the Creativity of PKK Women in Langensari Village - Rina Purwanti; Purwosiwi Pandansari (Asian Journal of Community Services, 2022)
The Covid outbreak has caused the community's economy to decline. This condition has motivated researchers to organize training that can improve the skills of people affected by Covid. the training that will be carried out is to make deliveries, especially those that have a selling value that can be utilized by residents of the Langensari Village. Through Peningset training, residents are expected to have skills and be able to open self-employment independently. This training was held to provide Peningset skills. The empowerment method used in this service is using the PAR (Participation Action Research) method. The scope of this service activity is PKK mothers. The service team is directly involved in the field as a teacher and companion.